Erbium-containing high-strength aluminum alloy capable of inhibiting additive manufacturing splashing and preparation method of erbium-containing high-strength aluminum alloy

By adjusting the chemical composition of aluminum alloy, the Mg element content is reduced and the Mn element content is increased. Combined with the addition of Si, Zr, Er, and Sc elements, the problems of splashing and black smoke in the additive manufacturing process are solved, and the machinery of aluminum alloy is improved The strength and forming quality achieve mechanical properties that match the prior art and even better than the prior art.

CN119410964AActive Publication Date: 2025-02-11AVIMETAL AM TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411599859.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-11
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

During the additive manufacturing process, Al-Mg and Al-Mn high-strength aluminum alloys are prone to splashing and black smoke problems, resulting in smoke and dust attached to the molding surface of the parts and the galvanometer surface, affecting the molding quality and mechanical strength.

Method used

By adjusting the chemical composition of the aluminum alloy, the Mg element content is reduced and the Mn element content is appropriately increased. Combined with the addition of Si, Zr, Er, and Sc elements, appropriate reinforced phases and nano-precipitation phases are formed to improve the mechanical strength and fluidity of the alloy. , reduce splashes and black smoke.

Benefits of technology

It effectively suppresses splashing and black smoke during the additive manufacturing process, improves the quality of the molding surface, ensures the mechanical strength of the aluminum alloy, and reaches a level that is the same as that of the existing technology or even better than the existing technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410964A_ABST
    Figure CN119410964A_ABST
Patent Text Reader

Abstract

The invention relates to an erbium-containing high-strength aluminum alloy for inhibiting additive manufacturing spatter and a preparation method thereof, and belongs to the technical field of additive manufacturing, the aluminum alloy comprises the following chemical components in percentage by mass: 2.0-3.5% of Mn element W (Mn), 0.5-1.5% of Mg, 0.5-1.5% of Si and the balance of Al; the content of the Mg element meets the following relation: 0.5% + 0.2 W (Mn) < = W (Mg) < = 2.0%; the content of the Si element meets the following relation: 0.1% + 0.05 W (Mn) < = W (Si) < = 0.3 W (Mn); and the balance of Al element. The problems of splashing, black smoke and the like caused by magnesium element volatilization in the printing process of the high-magnesium-content aluminum alloy and the problems that the high-manganese-content aluminum alloy is large in melt viscosity and powder is not easy to prepare can be solved, no black slag is left on the forming face of a printed part, and meanwhile the mechanical property of the prepared alloy meets the requirement that the tensile strength is not lower than 520 MPA.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of additive manufacturing, and in particular to an erbium-containing high-strength aluminum alloy capable of suppressing splashing in additive manufacturing and a preparation method thereof. Background Art

[0002] The high-strength aluminum alloy systems currently used in the field of laser additive manufacturing are mainly Al-Mg and Al-Mn. A certain amount of rare earth elements are added to form a strengthening phase diagram of refined grains to improve material strength. However, in the actual production process, it is found that Al-Mg alloys have more spatter during printing, and the smoke and dust formed are larger, which adheres to the forming surface of the parts and the surface of the galvanometer, causing more internal defects in the parts. In addition, Al-Mn alloys have a high amount of Mn elements added and the alloy liquid has a high viscosity. The guide tube is prone to blockage during the atomization powder making process, affecting production efficiency.

[0003] The invention patent with publication number CN114277285A discloses a high-strength aluminum alloy powder, the main components of which are Al-Mn-Mg-Sc, wherein the addition amount of Mn element is 4.2-6.0%, and the addition amount of Mg element is 1.2-3.0%. In this solution, excessive addition of manganese element makes the viscosity of aluminum liquid higher and powder making difficult.

[0004] The invention patent with the publication number CN117245084A discloses a 3D printed high-strength and heat-resistant aluminum alloy Al-Mg-Er-Zr. By adding rare earth elements Er, Fe, Si, etc., the problem of easy cracking in traditional Al-Mg alloy 3D printing is solved. However, in the high-strength aluminum alloy additive manufacturing process described in the above patent, it is found that when the size of the molded parts is large and the molding area is large, a large amount of splashes and smoke will be generated during the printing process. Some of them can enter the filtration system through the wind field, but most of the splashes fall on the molding surface. After a long period of printing, the smoke formed is adsorbed on the surface of the galvanometer, causing the laser power to decay. The laser reaching the molding surface cannot completely melt the current molding layer powder due to low heat input, and a large number of unfused defects appear inside the molded parts, affecting the final performance of the parts. After a large number of experimental analyses, it was found that the main reason for the large amount of splashes and black smoke in high-strength aluminum alloy materials is that the magnesium content in the alloy is too high. During the printing process, part of the magnesium element volatilizes to form black smoke, which adheres to the surface of the galvanometer, causing the laser power to decay. At the same time, a large amount of splashes are formed on the sintering surface, affecting the sintering quality of the molding surface. Summary of the invention

[0005] The purpose of the present invention is to provide an erbium-containing high-strength aluminum alloy and a preparation method thereof for suppressing splashing in additive manufacturing, which can solve the splashing and black smoke problems generated by the aluminum alloy system mentioned in the above background technology during the printing process, while ensuring the mechanical strength of the aluminum alloy.

[0006] To achieve the above object, the present invention provides the following technical solution: an erbium-containing high-strength aluminum alloy for suppressing splashing in additive manufacturing, the chemical composition of the aluminum alloy includes Mn, Mg, Si and Al elements, calculated by mass percentage:

[0007] The content of the Mn element W (Mn) is 2.0-3.5%;

[0008] The content of the Mg element and the content of the Mn element satisfy the following relationship: 0.5%+0.2W(Mn)≤W(Mg)≤2.0%;

[0009] The content of the Si element and the content of the Mn element satisfy the following relationship: 0.1%+0.05W(Mn)≤W(Si)≤0.3W(Mn);

[0010] The balance is Al element.

[0011] In a preferred embodiment, the chemical composition of the aluminum alloy further includes Zr, Er and Sc elements.

[0012] In a preferred embodiment, the Er element content W(Er) is 0.61-1.5%, the Sc element content W(Sc) is 0.2-0.6%, and the Zr element content and the Er, Sc, and Mn element contents satisfy the following relationship: 0.8W(Sc)+0.6W(Er)-0.05W(Mn)≤W(Zr)≤1.0%+0.1W(Mn).

[0013] In a preferred embodiment, the chemical composition of the aluminum alloy further includes Fe element.

[0014] In a preferred embodiment, the content of the Fe element and the content of the Si element satisfy the following relationship, measured in mass percentage: W(Si)+W(Fe)=0.4-1.0%.

[0015] Another aspect of the present invention provides a method for preparing an erbium-containing high-strength aluminum alloy for suppressing splashing during additive manufacturing, comprising the following steps:

[0016] S1. Alloy smelting: smelting aluminum alloy ingots or element materials that meet the composition requirements to obtain aluminum alloy liquid;

[0017] S2, powder atomization: using the aluminum alloy liquid to atomize and prepare powder;

[0018] S3, powder post-processing: the high-strength aluminum alloy powder obtained after atomization is subjected to classification processing;

[0019] S4. Additive manufacturing: The classified high-strength aluminum alloy powder of the target particle size segment is melted and molded to obtain a high-strength aluminum alloy product.

[0020] In a preferred embodiment, in step S1, the smelting temperature is 800-1000°C.

[0021] In a preferred embodiment, in step S2, the atomization pressure of atomization powder making is 3-5 MPa, and the atomization nozzle structure used in the atomization process is a hole-slot composite structure.

[0022] In a preferred embodiment, in step S3, the target particle size range of the classification treatment is 15-53 μm or 20-63 μm.

[0023] In a preferred embodiment, in step S4, the high-strength aluminum alloy powder is melt-formed by laser powder bed, the laser power is 300-400 W, the scanning speed is 900-1500 mm / s, the scanning interval is 0.08-0.12 mm, and the layer thickness is 0.03-0.06 mm.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The technical solution provided by the present invention reduces the content of Mg element to avoid the problem of splashing and black smoke, and at the same time appropriately increases the content of Mn element to compensate for the loss of mechanical strength of aluminum alloy products caused by the reduction of Mg element content. Specifically, Mg and Mn mainly play the role of solid solution strengthening and precipitation strengthening in aluminum alloys. Mn element can form Al6Mn phase with Al matrix to achieve precipitation strengthening and improve alloy strength. After the Mg content is reduced, the Mn element content is appropriately increased to form Al6Mn strengthening phase during heat treatment to compensate for the strength loss caused by the reduction of Mg content.

[0026] 2. The present invention can improve the problem of high melt viscosity and difficulty in pouring caused by excessively high Mn content by adding an appropriate amount of Si element, and reduce the generation of printing cracks. Specifically, the solubility of Mn in aluminum alloy is about 1.5%. If the amount of Mn added is too high, it is easy to increase the precipitated particles, form more solid phases, and increase the viscosity of the aluminum alloy melt. In this technical solution, an appropriate amount of Si element is added, and the addition relationship between Si content and Mn content is established. On the one hand, the increase in Si content can narrow the solidification range of the aluminum alloy melt and reduce the generation of printing cracks. On the other hand, by adding Si element, the segregation tendency of alloy elements in the solidification process can be reduced, the thermal conductivity of the aluminum alloy can be effectively improved, and the heat distribution in the aluminum alloy melt can be more uniform, which effectively improves the melt fluidity and solves the problem of high melt viscosity caused by excessively high Mn content in the atomization powder making process.

[0027] 3. Zr and rare earth elements Er and Sc are added in combination, and Al3 (Er / Sc / Zr) nano-precipitated phase is formed after heat treatment, which further increases the strength of the alloy. However, both Zr and Mn elements can improve the strength of the alloy. For every 0.1% increase in Zr content, the strength of the aluminum alloy increases by 10-20MPa, and for every 0.5% increase in Mn content, the strength of the alloy increases by 30-50MPa. Therefore, when the manganese element is increased, the zirconium element content should be appropriately reduced. The present invention establishes a corresponding relationship between the minimum and maximum addition amounts of zirconium elements and manganese elements, which can avoid problems such as printing cracking caused by excessive alloy strength.

[0028] In summary, the high-strength aluminum alloy provided by the present invention avoids the problems of splashing and black smoke by reducing the Mg content, but the solid solution strengthening effect of the Mg element is weakened, and the alloy strength is reduced. The increased Mn element increases the alloy strength by forming an Al6Mn strengthening phase, and the Er, Zr, and Sc elements form an Al3 (Er / Sc / Zr) nano-strengthening phase, which can further improve the alloy strength, so that the mechanical properties of the high-strength aluminum alloy in the present technical solution are not affected; at the same time, a proportional relationship between the Si content and the amount of Mn element added is established. The increase in the Mn content and the simultaneous increase in the Si element content can improve the problems of high melt viscosity and difficulty in pouring caused by the excessively high proportion of the Mn content. This solution can effectively solve the problems of black smoke formed by the volatilization of magnesium elements during the printing process of Al-Mg series high-strength aluminum alloys, which affects the molding quality of printed parts, and the high viscosity of the melt of Al-Mn series high-strength aluminum alloys, and the difficulty in preparing powder. The high-strength aluminum alloy provided by the present invention significantly reduces splashing and smoke during printing, and the molding surface of the printed parts presents a metallic luster without any black slag residue. At the same time, the mechanical properties of the prepared aluminum alloy are not affected, and its performance can be comparable to or even better than that of the prior art. After heat treatment, the tensile strength of the material is still not less than 520MPa, and the elongation is not less than 12%. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a photo of the printing process of Example 1 of the present invention;

[0030] Figure 2 This is a photo of the printing process of Example 2 of the present invention;

[0031] Figure 3 This is a photo of the printing process of Example 3 of the present invention;

[0032] Figure 4 This is a photo of the printing process of Example 4 of the present invention;

[0033] Figure 5 This is a photo of the printing process of Example 5 of the present invention;

[0034] Figure 6This is a photo of the printing process of Comparative Example 1 of the present invention;

[0035] Figure 7 This is a photo of the printing process of Comparative Example 2 of the present invention;

[0036] Figure 8 This is a photo of the printing process of Comparative Example 3 of the present invention;

[0037] Fig. 9 This is a photo of the internal metallographic structure of Comparative Example 3 of the present invention;

[0038] Fig.10 This is a photo of the printing process of Comparative Example 4 of the present invention;

[0039] Fig.11 This is a photo of the internal metallographic structure of Comparative Example 5 of the present invention. DETAILED DESCRIPTION

[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The present invention discloses an erbium-containing high-strength aluminum alloy for suppressing splashing in additive manufacturing, comprising Mn, Mg, Si, Al, Zr, Er, Sc, and Fe elements, calculated by mass percentage:

[0042] The content of the Mn element W (Mn) is 2.0-3.5%;

[0043] The content of the Mg element and the content of the Mn element satisfy the following relationship: 0.5%+0.2W(Mn)≤W(Mg)≤2.0%;

[0044] The content of the Si element and the content of the Mn element satisfy the following relationship: 0.1%+0.05W(Mn)≤W(Si)≤0.3W(Mn);

[0045] The content of the Er element W(Er) is 0.61-1.5%;

[0046] The content of the Sc element W(Sc) is 0.2-0.6%;

[0047] The content of the Zr element and the content of the Er element, the Sc element, and the Mn element satisfy the following relationship: 0.8W(Sc)+0.6W(Er)-0.05W(Mn)≤W(Zr)≤1.0%+0.1W(Mn);

[0048] The content of the Fe element and the content of the Si element satisfy the following relationship: W(Si)+W(Fe)=0.4-1.0%;

[0049] The balance is Al element.

[0050] Another aspect of the present invention provides a method for preparing an erbium-containing high-strength aluminum alloy for suppressing splashing during additive manufacturing, comprising the following steps:

[0051] S1. Alloy smelting: placing an aluminum alloy ingot or element material that meets the above composition requirements into a crucible for smelting to obtain an aluminum alloy liquid;

[0052] S2, powder atomization: pouring aluminum alloy liquid into the tundish crucible for atomization and powdering;

[0053] S3, powder post-processing: the high-strength aluminum alloy powder obtained after atomization is subjected to classification processing according to the particle size requirements;

[0054] S4. Additive manufacturing: The high-strength aluminum alloy powder of the target particle size segment obtained by screening is melt-molded by laser powder bed to obtain high-strength aluminum alloy products.

[0055] Specifically, in step S1, the smelting temperature is 800-1000°C;

[0056] In step S2, the atomization pressure of atomization powder making is 3-5 MPa, and the atomization nozzle structure used in the atomization process is a hole-slit composite structure;

[0057] In step S3, the target particle size range of the classification treatment is 15-53 μm or 20-63 μm, and the frequency used by the screening equipment is 20-35 Hz;

[0058] In step S4, the laser power used is 300-400W, the scanning speed is 900-1500mm / s, the scanning interval is 0.08-0.12mm, and the layer thickness is 0.03-0.06mm; the heat treatment system used is 280-350°C, and the temperature is kept for 2-5 hours and then air-cooled.

[0059] The present invention is further described in detail below in conjunction with the embodiments. It should also be understood that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0060] Example 1

[0061] The chemical composition of the high-strength aluminum alloy is calculated by mass percentage as follows: W(Mn): 2.0%; W(Mg): 1.0%; W(Er): 0.65%; W(Sc): 0.2%; W(Zr): 0.5%; W(Fe): 0.25%; W(Si): 0.25%; the balance is Al.

[0062] The high-strength aluminum alloy preparation method is as follows:

[0063] S1. Alloy smelting: The element materials are proportioned according to the above-mentioned composition requirements, and Al ingots, Al-Mg, Al-Mn, Al-Si, Al-Fe, Al-Er, Al-Zr, and Al-Sc binary alloy materials meeting the above-mentioned proportions are placed in a crucible for smelting to obtain aluminum alloy liquid. The smelting temperature is 800° C. and the holding time is 30 min.

[0064] S2: Powder atomization: Pour the aluminum alloy liquid into the tundish crucible for atomization and powdering. The atomization pressure is 3MPa, and the atomization nozzle structure used is a hole-slot composite structure;

[0065] S3: Powder post-processing: The high-strength aluminum alloy powder obtained after atomization is graded according to the particle size requirements. The powder particle size is 15-53μm and the screening frequency is 25HZ;

[0066] S4: Additive manufacturing: The high-strength aluminum alloy powder of the target particle size segment obtained by screening was subjected to laser powder bed melting to prepare high-strength aluminum alloy products. The laser power used was 300W, the scanning speed was 900mm / s, the scanning interval was 0.12mm, the printing layer thickness was 0.03mm, the heat treatment system used was 280℃, and it was air-cooled after keeping warm for 2 hours.

[0067] The specific data of the high-strength aluminum alloy printed samples, such as density, room temperature tensile strength, yield strength, and elongation, are shown in Table 1. The printing process photos are shown in Figure 1 .

[0068] Example 2

[0069] The elements in the high-strength aluminum alloy are calculated by mass percentage as follows: W(Mn): 2.3%; W(Mg): 1.3%; W(Er): 0.85%; W(Sc): 0.3%; W(Zr): 0.7%; W(Fe): 0.3%; W(Si): 0.35%, and the balance is Al.

[0070] The high-strength aluminum alloy preparation method is as follows:

[0071] S1. Alloy smelting: The element materials are proportioned according to the above-mentioned composition requirements, and Al ingots, Al-Mg, Al-Mn, Al-Si, Al-Fe, Al-Er, Al-Zr, and Al-Sc binary alloy materials meeting the above-mentioned proportions are placed in a crucible for smelting to obtain aluminum alloy liquid. The smelting temperature is 850° C. and the holding time is 20 min.

[0072] S2: Powder atomization: Pour the aluminum alloy liquid into the tundish crucible for atomization and powdering. The atomization pressure is 3.5MPa, and the atomization nozzle structure used is a hole-slot composite structure;

[0073] S3: Powder post-processing: The high-strength aluminum alloy powder obtained after atomization is graded according to the particle size requirements. The powder particle size is 20-63μm and the screening frequency is 30HZ;

[0074] S4: Additive manufacturing: The high-strength aluminum alloy powder of the target particle size segment obtained by screening is subjected to laser powder bed melting to prepare high-strength aluminum alloy products. The laser power used is 320W, the scanning speed is 1000mm / s, the scanning interval is 0.1mm, the printing layer thickness is 0.04mm, the heat treatment system used is 300℃, and it is air-cooled after keeping warm for 5 hours.

[0075] The specific data of the high-strength aluminum alloy printed samples, such as density, room temperature tensile strength, yield strength, and elongation, are shown in Table 1. The printing process photos are shown in Figure 2 .

[0076] Example 3

[0077] The elements in the high-strength aluminum alloy are calculated by mass percentage as follows: W(Mn): 2.75%; W(Mg): 1.5%; W(Er): 1.05%; W(Sc): 0.4%; W(Zr): 0.9%; W(Fe): 0.35%; W(Si): 0.4%, and the balance is Al.

[0078] The high-strength aluminum alloy preparation method is as follows:

[0079] S1. Alloy smelting: The element materials are proportioned according to the above-mentioned composition requirements, and Al ingots, Al-Mg, Al-Mn, Al-Si, Al-Fe, Al-Er, Al-Zr, and Al-Sc binary alloy materials meeting the above-mentioned proportions are placed in a crucible for smelting to obtain aluminum alloy liquid. The smelting temperature is 900° C. and the holding time is 20 min.

[0080] S2: Powder atomization: Pour the aluminum alloy liquid into the tundish crucible for atomization and powdering. The atomization pressure is 4MPa, and the atomization nozzle structure used is a hole-slot composite structure;

[0081] S3: Powder post-processing: The high-strength aluminum alloy powder obtained after atomization is graded according to the particle size requirements. The powder particle size is 20-63μm and the screening frequency is 30HZ;

[0082] S4: Additive manufacturing: The high-strength aluminum alloy powder of the target particle size segment obtained by screening is subjected to laser powder bed melting to prepare high-strength aluminum alloy products. The laser power used is 350W, the scanning speed is 1100mm / s, the scanning interval is 0.11mm, the printing layer thickness is 0.03mm, the heat treatment system used is 300℃, and it is air-cooled after keeping warm for 2 hours.

[0083] The specific data of the high-strength aluminum alloy printed samples, such as density, room temperature tensile strength, yield strength, and elongation, are shown in Table 1. The printing process photos are shown in Figure 3 .

[0084] Example 4

[0085] The elements in the high-strength aluminum alloy are calculated by mass percentage as follows: W(Mn): 3.05%; W(Mg): 1.75%; W(Er): 1.25%; W(Sc): 0.5%; W(Zr): 1.1%; W(Fe): 0.4%; W(Si): 0.5%; and the balance is Al.

[0086] The high-strength aluminum alloy preparation method is as follows:

[0087] S1. Alloy smelting: The element materials are proportioned according to the above-mentioned composition requirements, and Al ingots, Al-Mg, Al-Mn, Al-Si, Al-Fe, Al-Er, Al-Zr, and Al-Sc binary alloy materials meeting the above-mentioned proportions are placed in a crucible for smelting to obtain aluminum alloy liquid. The smelting temperature is 950° C. and the holding time is 15 min.

[0088] S2: Powder atomization: Pour the aluminum alloy liquid into the tundish crucible for atomization and powdering. The atomization pressure is 4.5MPa, and the atomization nozzle structure used is a hole-slit composite structure;

[0089] S3: Powder post-processing: The high-strength aluminum alloy powder obtained after atomization is graded according to the particle size requirements. The powder particle size is 15-53μm and the screening frequency is 35HZ;

[0090] S4: Additive manufacturing: The high-strength aluminum alloy powder of the target particle size segment obtained by screening is subjected to laser powder bed melting to prepare high-strength aluminum alloy products. The laser power used is 375W, the scanning speed is 1200mm / s, the scanning interval is 0.1mm, the printing layer thickness is 0.04mm, the heat treatment system used is 325℃, and it is air-cooled after keeping warm for 5 hours.

[0091] The specific data of the high-strength aluminum alloy printed samples, such as density, room temperature tensile strength, yield strength, and elongation, are shown in Table 1. The printing process photos are shown in Figure 4 .

[0092] Example 5

[0093] The elements in the high-strength aluminum alloy are calculated by mass percentage as follows: W(Mn): 3.45%; W(Mg): 1.95%; W(Er): 1.5%; W(Sc): 0.6%; W(Zr): 1.3%; W(Fe): 0.35%; W(Si): 0.6%; and the balance is Al.

[0094] The high-strength aluminum alloy preparation method is as follows:

[0095] S1. Alloy smelting: The element materials are proportioned according to the above-mentioned composition requirements, and Al ingots, Al-Mg, Al-Mn, Al-Si, Al-Fe, Al-Er, Al-Zr, and Al-Sc binary alloy materials meeting the above-mentioned proportions are placed in a crucible for smelting to obtain aluminum alloy liquid. The smelting temperature is 1000° C. and the holding time is 15 min.

[0096] S2: Powder atomization: Pour the aluminum alloy liquid into the tundish crucible for atomization and powdering. The atomization pressure is 5MPa, and the atomization nozzle structure used is a hole-slot composite structure;

[0097] S3: Powder post-processing: The high-strength aluminum alloy powder obtained after atomization is graded according to the particle size requirements. The powder particle size is 15-53μm and the screening frequency is 30HZ;

[0098] S4: Additive manufacturing: The high-strength aluminum alloy powder of the target particle size segment obtained by screening is subjected to laser powder bed melting to prepare high-strength aluminum alloy products. The laser power used is 400W, the scanning speed is 1500mm / s, the scanning spacing is 0.08mm, the printing layer thickness is 0.04mm, the heat treatment system used is 350℃, and it is air-cooled after keeping warm for 5 hours.

[0099] The specific data of the high-strength aluminum alloy printed samples, such as density, room temperature tensile strength, yield strength, and elongation, are shown in Table 1. The printing process photos are shown in Figure 5 .

[0100] Comparative Example 1 (High Mg Content)

[0101] Except that the Mg content is higher than that in Example 3, the other conditions in this comparative example are the same as those in Example 3.

[0102] The chemical composition of the high-strength aluminum alloy powder in this comparative example is: W(Mn): 2.75%; W(Mg): 3.5%; W(Er): 1.05%; W(Sc): 0.4%; W(Zr): 0.9%; W(Fe): 0.35%; W(Si): 0.4%, and the balance is Al.

[0103] The specific data of the printed samples, such as density, room temperature tensile strength, yield strength, and elongation, are shown in Table 1. The printing process photos are shown in Figure 6 .

[0104] Comparative Example 2 (high Mn content)

[0105] Except that the Mn content is higher than that in Example 3, the other conditions in this comparative example are the same as those in Example 3.

[0106] The chemical composition of the high-strength aluminum alloy powder in this comparative example is: W(Mn): 4.0%; W(Mg): 1.5%; W(Er): 1.05%; W(Sc): 0.4%; W(Zr): 0.9%; W(Fe): 0.35%; W(Si): 0.4%, and the balance is Al.

[0107] The specific data of the printed samples, such as density, room temperature tensile strength, yield strength, and elongation, are shown in Table 1. The printing process photos are shown in Figure 7 .

[0108] Comparative Example 3 (without Si element)

[0109] The chemical composition of the high-strength aluminum alloy powder in this comparative example does not include Si element, and the other conditions are the same as those in Example 3.

[0110] The chemical composition of the high-strength aluminum alloy powder in this comparative example is: W (Mn): 2.75%; W (Mg): 1.5%; W (Er): 1.05%; W (Sc): 0.4%; W (Zr): 0.9%; W (Fe): 0.35%; the balance is Al.

[0111] The specific data of the printed samples, such as density, room temperature tensile strength, yield strength, and elongation, are shown in Table 1. The printing process photos are shown in Figure 8 , internal metallographic structure photos see Fig. 9 .

[0112] Comparative Example 4 (low Mn content)

[0113] Except that the Mn content is lower than that in Example 3, the other conditions in this comparative example are the same as those in Example 3.

[0114] The chemical composition of the high-strength aluminum alloy powder in this comparative example is: W(Mn): 1.5%; W(Mg): 1.5%; W(Er): 1.05%; W(Sc): 0.4%; W(Zr): 0.9%; W(Fe): 0.35%; W(Si): 0.4%; the balance is Al.

[0115] The specific data of the printed samples, such as density, room temperature tensile strength, yield strength, and elongation, are shown in Table 1. The printing process photos are shown in Fig.10 .

[0116] Comparative Example 5 (Zr content is high)

[0117] Except that the Zr content is higher than that in Example 3, the other conditions in this comparative example are the same as those in Example 3.

[0118] The chemical composition of the high-strength aluminum alloy powder in this comparative example is: W(Mn): 2.75%; W(Mg): 1.5%; W(Er): 1.05%; W(Sc): 0.4%; W(Zr): 1.4%; W(Fe): 0.35%; W(Si): 0.4%; the balance is Al.

[0119] The specific data of the printed sample, such as density, room temperature tensile strength, yield strength, and elongation, are shown in Table 1. The internal metallographic structure photos are shown in Fig.11 .

[0120] The specific data of the density, room temperature tensile strength, yield strength, elongation, etc. of the high-strength aluminum alloy printed samples prepared in the above Examples 1-5 and Comparative Examples 1-4 are shown in Table 1.

[0121] Table 1 Mechanical properties data of aluminum alloy samples obtained in Examples and Comparative Examples

[0122]

[0123]

[0124] It can be seen from Examples 1-5 that the internal density of the aluminum alloy samples provided by the embodiments of the present invention is above 99.5%, and after heat treatment, the room temperature tensile strength of the samples is above 520 MPa, and the elongation is above 12%. Figure 1-Figure 5 It can be seen from the printing process photos that no obvious smoke and black residue exist in the actual molding process of each embodiment.

[0125] By comparing Example 3 with Comparative Example 1, it can be seen that when the magnesium content is increased, the mechanical properties of the printed part are significantly improved, and the tensile strength reaches 570Mpa. Figure 6It can be seen that due to the high magnesium content, a lot of smoke appeared during the printing process, and there was a lot of black slag on the sintering surface, and the elongation of the material was reduced, indicating that there were many defects inside the printed sample.

[0126] By comparing Example 3 with Comparative Example 2, it can be seen that after increasing the manganese content, the performance of the printed part is slightly improved. Figure 7 It can be seen that there was no large amount of smoke and black slag during the printing process, but this batch of powder had a high Mn content, the aluminum alloy melt had a high viscosity, the guide tube was clogged during the powder making process, and the production process had continuity deviations.

[0127] Compare Example 3 with Comparative Example 3, and combine Figure 8 and Fig. 9 It can be seen that when silicon is not added to the alloy, there is no obvious smoke during the printing process, but there is black slag at the edge of the sample. From the metallographic structure, it is found that there are a large number of microcracks inside the sample, the strength and elongation of the printed parts are significantly reduced, and the flow guide tube is blocked during the powder making process of this batch of powder. This shows that adding a small amount of silicon is beneficial to improving the fluidity of aluminum alloy melt, narrowing the solidification range, and reducing the generation of printing cracks.

[0128] Comparative Example 3 and Comparative Example 4, and combined Fig.10 It can be seen that when the manganese content in the alloy decreases, there is no obvious smoke and black slag during the printing process of the sample, but the strength of the printed part is lower than 520MPa, which shows that the manganese content helps to improve the strength of the material.

[0129] Comparative Example 3 and Comparative Example 5, and combined Fig.11 It can be seen that when the Zr content in the alloy is high, the material strength is improved, and a large amount of Zr element segregation appears in the metallographic structure inside the printed test block ( Fig.11 White particles in the alloy) and micro cracks affect the comprehensive mechanical properties of the alloy.

[0130] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. An erbium-containing high-strength aluminum alloy for suppressing splashing in additive manufacturing, characterized in that: The chemical composition of the aluminum alloy includes Mn, Mg, Si and Al elements, calculated by mass percentage: The content of the Mn element W (Mn) is 2.0-3.5%; The content of the Mg element and the content of the Mn element satisfy the following relationship: 0.5%+0.2W(Mn)≤W(Mg)≤2.0%; The content of Si element and the content of Mn element satisfy the following relationship: 0.1%+0.05W(Mn)≤W(Si)≤ 0.3W(Mn); The balance is Al element.

2. The erbium-containing high-strength aluminum alloy for suppressing splashing in additive manufacturing according to claim 1, characterized in that: The chemical composition of the aluminum alloy also includes Zr, Er and Sc elements.

3. The erbium-containing high-strength aluminum alloy for suppressing splashing in additive manufacturing according to claim 2, characterized in that: Calculated by mass percentage, the content of the Er element W(Er) is 0.61-1.5%, the content of the Sc element W(Sc) is 0.2-0.6%, and the content of the Zr element and the contents of the Er, Sc and Mn elements satisfy the following relationship: 0.8W(Sc)+0.6W(Er)-0.05W(Mn)≤W(Zr)≤1.0%+0.1W(Mn).

4. The erbium-containing high-strength aluminum alloy for suppressing splashing in additive manufacturing according to claim 1, characterized in that: The chemical composition of the aluminum alloy also includes Fe element.

5. The erbium-containing high-strength aluminum alloy for suppressing splashing in additive manufacturing according to claim 4, characterized in that: In terms of mass percentage, the content of the Fe element and the content of the Si element satisfy the following relationship: W(Si)+W(Fe)=0.4-1.0%.

6. The method for preparing an erbium-containing high-strength aluminum alloy for suppressing splashing in additive manufacturing according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Alloy smelting: smelting aluminum alloy ingots or element materials that meet the composition requirements to obtain aluminum alloy liquid; S2, powder atomization: using the aluminum alloy liquid to atomize and prepare powder; S3, powder post-processing: the high-strength aluminum alloy powder obtained after atomization is subjected to grading treatment; S4. Additive manufacturing: The classified high-strength aluminum alloy powder of the target particle size segment is melted and molded to obtain a high-strength aluminum alloy product.

7. The method for preparing an erbium-containing high-strength aluminum alloy for suppressing splashing in additive manufacturing according to claim 6, characterized in that: In step S1, the smelting temperature is 800-1000°C.

8. The method for preparing an erbium-containing high-strength aluminum alloy for suppressing splashing in additive manufacturing according to claim 6, characterized in that: In step S2, the atomization pressure of atomization powder making is 3-5 MPa, and the atomization nozzle structure used in the atomization process is a hole-slot composite structure.

9. The method for preparing an erbium-containing high-strength aluminum alloy for suppressing splashing in additive manufacturing according to claim 6, characterized in that: In step S3, the target particle size range of the classification treatment is 15-53 μm or 20-63 μm.

10. The method for preparing an erbium-containing high-strength aluminum alloy for suppressing splashing in additive manufacturing according to claim 6, characterized in that: In step S4, the high-strength aluminum alloy powder is melt-formed by laser powder bed, with a laser power of 300-400 W, a scanning speed of 900-1500 mm / s, a scanning interval of 0.08-0.12 mm, and a layer thickness of 0.03-0.06 mm.

Citation Information

Patent Citations

  • High-strength aluminum alloy powder, application of high-strength aluminum alloy powder in 3D printing and 3D printing method of high-strength aluminum alloy powder

    CN114277285A

  • High-strength aluminum alloy powder for 3D printing and preparation method thereof

    CN113684403A

  • High-strength temperature-resistant aluminum alloy powder for 3D printing as well as preparation method and application of high-strength temperature-resistant aluminum alloy powder

    CN117245084A

  • Aluminium alloy and process for additive manufacture of lightweight components

    US20220168811A1

  • Induction-type reaction rails for high speed trains

    US3891433A